Respostas
respondido por:
1
Resposta:
Resolução:
\frac{(x - 5)}{10} + \frac{(1 - 2x)}{5} = \frac{(3 - x)}{4}10(x−5)+5(1−2x)=4(3−x)
mmc = 20mmc=20
\frac{(2x - 10)}{20} + \frac{(4 - 8x)}{20} = \frac{(15 - 5x)}{20}20(2x−10)+20(4−8x)=20(15−5x)
2x - 10 + 4 - 8x = 15 - 5x2x−10+4−8x=15−5x
2x - 8x + 5x = 15 + 10 - 42x−8x+5x=15+10−4
- 6x + 5x = 25 - 4−6x+5x=25−4
- x = 21 \: \times ( - 1)−x=21×(−1)
x = - 21x=−21
espero ter ajudado
Perguntas similares
5 anos atrás
5 anos atrás
5 anos atrás
7 anos atrás
8 anos atrás
8 anos atrás